Aspectos clínicos e epidemiológicos da infecção pelo Papilomavírus Humano (HPV) em mulheres da população urbana e ribeirinha no município de Santarém-PA - LIMA, Maria Mônica Machado de Aguiar (Universidade Federal do Pará, 2017)
The human papilloma virus (HPV) is a virus that infects the skin and mucosa and is associated with cancer of the cervix, by increasing the likelihood of this happening, but parallel to this, other behavioral risk factors should be investigated. Focusing research on the prevalence and the clinical epidemiology of genital infection by HPV in women of urban and riverside municipality of Santarém-Para State proposed a comparative study to be observational, descriptive and analytical , transversal, where there was a selection of 511 women, with 391 women (38.54 ± 11.4 years) and 120 for Urban sample comprised the sample riverfront (37.2 ± 11.7 years). For data collection an interview was conducted, containing information about the factors that may be associated with the incidence of HPV and cervical cancer, plus a collection of biological material that was analyzed by cytology, DNA isolation and PCR . The analysis of these data was performed using the tab in excel and subsequent treatment through statistical software Bioestat 5.0, with the results a low prevalence of HPV compared with surveys from other regions, and homogeneity of results between urban and riverside, differing only in the topics of education, smoking status, number of sexual partners during their lifetime, and oral contraceptive used during life. Concluding that despite geographical location, there is for the municipality of Santarém a big change in the profile of woman between data found in the urban area and the waterfront on the epidemiology of HPV.